The Problems of Consumerʼs Protection in the Financial Market in Ukraine: Empirical Research - Lobozynska, Sophia (Journal of Finance and Financial Law, 2017)
The article presents the results of empirical research of rights protection of consumer of financial services in Ukraine. It revealed the scope and nature of the violations of the rights of financial services consumers, and the actions of the respondents for the protection of their rights. Special attention is focused on identifying the level of financial literacy of people and finding effective tools of consumer rights protection. The need for the development and adoption of the National Strategy for rights protection of consumers of financial services market and increasing of financial literacy were proved.